2001
DOI: 10.1046/j.1365-8711.2001.04836.x
|View full text |Cite
|
Sign up to set email alerts
|

Cumulenic and heterocumulenic anions: potential interstellar species?

Abstract: A recent theoretical investigation by Terzieva & Herbst of linear carbon chains, Cn where n ≥ 6, in the interstellar medium has shown that these species can undergo efficient radiative association to form the corresponding anions. An experimental study by Barckholtz, Snow & Bierbaum of these anions has demonstrated that they do not react efficiently with molecular hydrogen, leading to the possibility of detectable abundances of cumulene‐type anions in dense interstellar and circumstellar environments. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
1
23
1
Order By: Relevance
“…The strong similarity between the averaged line profiles of both molecules indicates that C 4 H and its anion are spatially coexistent. Adopting for C 4 H − a permanent dipole moment µ = 6.2 D (Botschwina, quoted by Blanksby et al 2001), we derive a rotational temperature T rot (C 4 H − ) = 23 ± 2 K, somewhat lower than that of C 4 H, and a column density N(C 4 H − ) = 7.1 ± 2.0 × 10 11 cm −2 (see Fig. 3), which yields N(C 4 H − )/N(C 4 H) = 1/4200.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strong similarity between the averaged line profiles of both molecules indicates that C 4 H and its anion are spatially coexistent. Adopting for C 4 H − a permanent dipole moment µ = 6.2 D (Botschwina, quoted by Blanksby et al 2001), we derive a rotational temperature T rot (C 4 H − ) = 23 ± 2 K, somewhat lower than that of C 4 H, and a column density N(C 4 H − ) = 7.1 ± 2.0 × 10 11 cm −2 (see Fig. 3), which yields N(C 4 H − )/N(C 4 H) = 1/4200.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, k ratt is high for large molecules with a high EA. Among those, the polyacetylenic chain families C 2n H, which have exceptionally large electron affinities (EA ≥ 3 eV, Blanksby et al 2001) and whose smallest members had just been observed in IRC +10216 (Guélin et al 1978) and in the dark cloud TMC-1 (Guélin et al 1982), stuck out as the most likely progenitors of large interstellar anions. It is remarkable that with this simple reasoning, Herbst (1981) predicted 26 years ago that C 4 H − and, more generally, C 2n H − (n ≥ 2) may be abundant in interstellar and circumstellar clouds ([C 2 nH − ]/[C 2 nH] = 0.1−0.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of negative ions in the interstellar medium was predicted many years ago on general grounds or on the basis of ion-molecule chemical models (see, for example, Dalgarno and McCray 1973;Herbst 1981;Millar et al 2000;Blanksby et al 2001). It was pointed out that a high electron affinity and a large number of vibrational states increase greatly the sticking coefficient of electrons; for instance, large, negatively charged carbon chains of the form C n H -were predicted to be quite abundant.…”
Section: Observation Of Ionic Speciesmentioning
confidence: 99%